Perancangan Dashboard Monitoring Painting Defect Berbasis Website - Rohmaniati; Heri Haerudin (CV. Multi Kreasi Media, 2022)
Monitoring is carried out to produce process continuity data to determine steps towards continuous improvement. Information is the result of processing data in a form that is more useful for the recipient. Information is very important for organizations or companies in the context of making decisions. However, in practice, organizations are still not able to present information systematically and easily so that valuable data sources are often neglected. PT Cakrawala Automotif Rabhasa (PT CAR) Authorized Body and Paint Center is an automotive body repair and painting service company located in the city of South Tangerang. In order to control the quality of performance results, PT CAR focuses on painting defects found during the quality control process as a reference. Unfortunately, the results of this quality control activity are still conveyed orally during briefings so they are not recorded regularly. This study designed a web-based dashboard application using the pure PHP programming language (native) which aims to make it easier to present and read information.